Agricultural Diversification through Contract Farming for Farmers’ Sustainable Welfare in Jember - Ajeng Pramesthy H.K; tegar raffi jumantoro; Emi Zulaika (Inicio Legis Fakultas Hukum Universitas Trunojoyo Madura, 2026)
Agricultural diversification is an important strategy for improving farmers’ welfare and supporting agricultural sustainability. One approach that has gained increasing attention is contract farming as a partnership scheme between farmers and agribusiness enterprises. However, its implementation in Jember Regency faces challenges, including low legal literacy among farmers, inadequate legal protection, and weak partnership institutions. This study aims to analyze the implementation of contract farming as a strategy for agricultural diversification and to formulate a legal policy model that supports its sustainability. Using a socio-legal approach with a qualitative method, the study finds that contract farming has not fully established balanced partnerships due to unequal bargaining positions, insufficient contractual protection, and the absence of adequate local regulations. Therefore, strengthening regulations, farmer protection, and partnership institutions is essential to support the sustainability of contract farming.